2006
DOI: 10.3168/jds.s0022-0302(06)72590-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DGAT1 Mutations and the CSN1S1 Promoter in the German Angeln Dairy Cattle Population

Abstract: The identification of quantitative trait loci (QTL) and genes with influence on milk production traits has been the objective of various mapping studies in the last decade. In the centromeric region of Bos taurus autosome (BTA) 14, the acyl-CoA:diacylglycerol acyltransferase1 gene (DGAT1) has been identified as the most likely causative gene underlying a QTL for milk fat yield and content. Recently, a second polymorphism in the promoter of DGAT1 emerged as an additional source of variation. In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
53
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 23 publications
11
53
2
1
Order By: Relevance
“…In the association analysis carried out without air temperature taken into account, the DGAT1:K232 allele significantly decreased milk and protein yields and increased fat yield and fat and protein contents (data not shown). These results are consistent with the findings of many previous studies performed in several dairy cattle populations (e.g., 6,8,13). To the best of the authors' knowledge, the influence of weather conditions on DGAT1 effects on milk yield and composition has not been investigated to date, although Duchemin et al (14) found significant K232A genotype by season interactions for some fatty acid contents in milk.…”
Section: Short Communicationsupporting
confidence: 82%
“…In the association analysis carried out without air temperature taken into account, the DGAT1:K232 allele significantly decreased milk and protein yields and increased fat yield and fat and protein contents (data not shown). These results are consistent with the findings of many previous studies performed in several dairy cattle populations (e.g., 6,8,13). To the best of the authors' knowledge, the influence of weather conditions on DGAT1 effects on milk yield and composition has not been investigated to date, although Duchemin et al (14) found significant K232A genotype by season interactions for some fatty acid contents in milk.…”
Section: Short Communicationsupporting
confidence: 82%
“…The regression analysis of the DGAT1 promoter VNTR alleles revealed significant effects for the allele 5 enhancing the milk fat content percentage as well as the milk protein percentage but decreasing the milk yield and milk protein yield (Kuhn et al 2004). Sanders et al (2006) reported 6 alleles found in the DGAT1 promoter VNTR in the Angeln population, which were denoted as VNTR alleles A, B, C, D, E, and F, respectively. The allele F was present in two unrelated daughters only.…”
Section: Introductionmentioning
confidence: 95%
“…The DGAT1 gene encodes the DGAT1 enzyme, which catalyzes the final step of triglyceride synthesis (Sanders et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Variable number of tandem repeat (VNTR) polymorphisms in the promoter region of the DGAT1 gene also seem to affect milk production traits, probably due to variation at the transcriptional level of the gene . A specific allele of the DGAT1 promoter VNTR showed significant effects on lactose yield and content and on milk energy content, compared with the other alleles (Sanders et al, 2006). DGAT1 and TG gene physically maps to the centromeric region of bovine chromosome 14 (Coppieters et al, 1998;Winter et al, 2002).…”
mentioning
confidence: 99%